(untitled) (Sains Humanika, 2013)
The implementation of home financing in Islamic banking system in Malaysia adapts various forms of Islamic financial instruments. It depends on the requirements and needs of a particular Islamic banks/financial institutions. Among the instruments that widely practiced are BayʻBithaman Ajil (BBA), Ijarah and others. However, in the recent years, there have been criticisms that questioned the aforementioned instruments in financing or refinancing a house. Thus, anew instrument has been introduced which is Musharakah Mutanaqisah contract. This contract has been practiced by selected Islamic banks in Malaysia. Since the contract is still in the early stage of implementation, it is the aim of this paper to critically analyse and explain the foundation, concept and the application of the contract that is applied in Home mortgage refinancing. This study focuses on the two major banks that already applied the contract; RHB Islamic Bank Berhad (RHBIBB) and Maybank Islamic Berhad (MIB). Among other objective of this study is to clarify the question about the possibility to refinance a house if the contracts are occurred in two different banks for example, from RHBIB to MIB. In addition, this study is also to answer the main question of the existence of Inah element which is regarded as an important component in Muʻamalat. In conducting this research, a fully library research and interview surveys have been utilised in collecting the data. Interviews were conducted in the abovementioned banking institutions. Meanwhile, in analysing the data, different methods of analysis including inductive, deductive and comparative methods have been adopted. Findings from this analysis reveal that there are few issues arise as a result of the implementation of the Musharakah Mutanaqisah contract particularly in refinancing home mortgage. These include issue of ownership between a customer and a bank, where’s a bank is shared owner of the houses and also the problem of determination of the house’s price that is to be refinanced. From the findings, several suggestions have been recommended in order to refine the implementation of this contract.